ANALISIS PENGARUH PEMBAGIAN KERJA, INSENTIF, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PERANGKAT DESA - Indah Rohyani; Tri Lasmini Yulianti (FEB UNWIKU PURWOKERTO, 2021)
This study aims to determine the effect of the division of labor, incentives, and work motivation, on the performance of village officials Sruweng District Kebumen District.The problem raised in this study is the division of labor, incentives, and work motivation, on the performance of village apparatus employees in Sruweng District, Kebumen Regency, with the aim to find out how much influence the division of labor, incentives, and work motivation, on the performance of village apparatus employees in Sruweng District Kebumen partially or simultaneously.The sample data taken in this study were 55 employees of the village apparatus of Sruweng District, Kebumen District, as respondents. The instrument or data collection tool in this study was to use a questionnaire.Data analysis tools used in this study are using multiple linear regression analysis. Data analysis techniques used include qualitative analysis and quantitative analysis consisting of validity, reliability, t-test, F-test, multiple linear regression analysis (Likert scale ). Data were analyzed with the help of the SPSS Release 23 for Windows program.The results of the first hypothesis proving that the division of labor partially has a significant effect on performance. The second hypothesis results that incentives partially have a significant effect on performance. The results of the third hypothesis proving that work motivation partially has a significant effect on performance. The results of the work division hypothesis, incentives, and work motivation simultaneously